The Effect Of Tax Planning On Earnings Management Moderated By Tax Rate Reductions - Intan Kumala Ratu; Agrianti Komalasari; Liza Alvia (Cita konsultindo, 2025)
This study aims to analyze the effect of tax planning on earnings management and examine the role of tax rate reductions as a moderating variable. Secondary data were obtained from the annual reports of manufacturing companies in the Consumer Non-Cyclical subsector listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. Using a purposive sampling technique, 62 companies were selected out of a total of 67 that met the criteria, resulting in 372 observations. This research applies a quantitative approach using documentation methods and moderation regression analysis processed with SPSS version 27. The results show that tax planning has a significant and positive effect on earnings management, indicating that companies tend to engage in earnings management as tax efficiency increases through tax-saving strategies. However, when tax rate reduction is used as a moderating variable, the effect of tax planning on earnings management weakens. The tax rate reduction acts as a pure moderator that reduces the intensity of earnings management practices, as the incentive to manipulate earnings becomes lower. Thus, fiscal policies in the form of tax rate reductions can serve as an effective instrument to curb non-transparent financial reporting practices.